2016
DOI: 10.3109/23744235.2016.1169553
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and serovar profiling of non-typhoidal Salmonellae (NTS) isolated from gastroenteritis cases–A study from South India

Abstract: Human infection with non-typhoidal Salmonella (NTS) serovars is often a neglected and undiagnosed infection in the developing world. Invasive NTS is now being established as having a new and emerging pathogenic role. There is not sufficient data on the prevalence of NTS serovars and their antibiotic susceptibility pattern from India. Faecal specimens collected from patients with acute gastroenteritis were processed to isolate Salmonella according to the standard protocol for a period from January 2011-December… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
1
7
2
Order By: Relevance
“…Among the NTS isolated from stool samples, Nalidixic acid was predominant among our NTS, (64.8%) which was very much higher than that reported from Kenya (6%) (16). In contrast to our results, other studies from South India (8), and West Africa (31), reported that none of their NTS isolates were resistant to nalidixic acid.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Among the NTS isolated from stool samples, Nalidixic acid was predominant among our NTS, (64.8%) which was very much higher than that reported from Kenya (6%) (16). In contrast to our results, other studies from South India (8), and West Africa (31), reported that none of their NTS isolates were resistant to nalidixic acid.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study ciprofloxacin resistance (47.8%) was the second most common resistance reported, which was higher than that reported from Ethiopia (4.5%) (34), Congo (4.3%) (33), India (23.5%) (22), and lower than that reported from South India (97%) (8). Other studies from West Africa (31) and Malaysia (35) reported 100% susceptibility to ciprofloxacin.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The predominant serovars identified in this study were Typhimurium and Kentucky. Both of these serovars were identified earlier from human infections in India [30]. Two Typhimurium strains isolated in this study were MDR with penta and tetra-type resistant patterns suggesting the significance of this serovar in animal and public health.…”
Section: Discussionsupporting
confidence: 54%
“…NTS isolated in India and other countries are generally susceptible to many antimicrobials (12,13,37). Except for S. Kentucky, the other NTS isolates from diarrheal patients from 2011 to 2014 in Manipal, south of India, were susceptible to most of the tested antimicrobials (38). S. Kentucky encountered in this study was highly resistant to many of antimicrobials and the resistance profiles increased in four years from 2014 to 2017.…”
Section: Discussionmentioning
confidence: 58%